ESG disclosure and firm performance: evidence after the revision of Malaysian code of corporate governance - Ab Aziz, Noor Hidayah; Abdul Latiff, Ahmed Razman; Alshdaifat, Sajead Mowafaq; Osman, Mohammad Noor Hisham; Azmi, Nurul Azlin (Human Resource Management Academic Research Society, 2023)
Environmental, Social and Governance (ESG) is one of the vital concerns in the current corporate environment. Firms must be transparent on ESG issues to create sustainable value and fulfill stakeholders’ rights. Since the late 2000s, many countries, including ASEAN countries, have mandated ESG disclosure to increase transparency. This study aims to examine the effect of ESG disclosure on firm performance measured by profitability indicators among Malaysian public listed firms with the data collected from 2017 after the revision of the Malaysian corporate governance code from ‘comply and explain’ to ‘apply and explain’ until 2021. The data was gathered from the Thomson Reuters Eikon Database, which consists of ESG scores and firm profitability through ROA and ROE. Using OLS regression method, the results indicate that ESG disclosure positively and significantly affects ROA and ROE. While, the results of each individual pillar of ESG (environmental, social and governance) revealed that only ROA was strongly impacted by all the pillars, whereas ROE was only affected by the social pillar. Further analysis revealed firms with higher ESG disclosure perform superior to those with lower ESG disclosure. This study helps to enrich the knowledge of ESG disclosure and its effect on firm performance. Particularly this study will help Malaysian firms to strategies on ESG disclosure to realise its impact on performance. Besides, capital market regulators will also have a direction to impose regulations pertinent to ESG.